GAMBARAN TINGKAT KEPOSITIFAN BASIL TAHAN ASAM, ANGKA KONVERSI, DAN HASIL PENGOBATAN PADA PASIEN TUBERKULOSIS PARU KATEGORI I DI UP4 PROVINSI KALIMANTAN BARAT PERIODE 2009-2012 - ., Triponia Steffi Oktia (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background: In Indonesia, there are 429.730 new cases of TB and62.246 death because of TB every year. In sputum examination, sputumgrading assessed based on the number of acid fast bacili. Sputum gradingused to assess the degree of infectious in pulmonary tuberculosis patients.Smear conversion rate is an indicator used to monitor and assesstreatment of pulmonary tuberculosis. High conversion rate will be followedby higher cure rate.Objective: To describe sputum smear grading, smear conversion rate,and treatment outcome of pulmonary tuberculosis patients treated withcategory 1 regimen.Methods: This research used descriptive study with cross sectionalapproach. Data were taken from the medical records of TB patients whotreated category 1 regimen in 2009-2012. Univariate data analysis wasused to describe the distribution of gender, age, type of anti TB drugs,history of DM, sputum grading, conversion rate, and treatment outcome.Results: Distribution of the most subjects in this study were the male(58,82%), age between 22-28 years old (21,85%), type of anti TB drugsused fixed doses combination (85,72%), did not have diabetes mellitus(88,24%), and +1 of acid fast bacili grades (55,46%). Sputum conversionrate was found more than the national target. The most of treatmentoutcomes was cured (88,23%), and then were transferred out (5,04%),defaulted (3,36%), failure (2,52%), dan died (0,84%).Conclusion: Patients with higher grades of sputum positivity at thebegining of the treatment and lower sputum conversion rate at the endintensive phase have lower cure rate.Keyword: Sputum grading, Conversion rate, Treatment outcome1) Medical School, Faculty of Medicine, University of Tanjungpura,Pontianak, West Kalimantan.2) Department of Pulmonology, dr. Soedarso Hospital, Pontianak, WestKalimantan.3) Department of Nutrition, Faculty of Medicine, University ofTanjungpura, Pontianak, West Kalimantan.